UPAYA PENCEGAHAN ANEMIA MELALUI EDUKASI ASUPAN NUTRISI DAN SUPLEMENTASI TABLET TAMBAH DARAH PADA REMAJA PEREMPUAN - Annisa Lidra Maribeth; Widia Sari; Rialta Hamda; Ghaniyyatul Khudri; Kurnia Maidarmi Handayani (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
Anemia is a common health problem worldwide, particularly among adolescent girls. This group is at high risk of anemia due to menstruation during adolescence, which leads to blood loss. Additionally, the increased need for iron in adolescent girls contributes to their vulnerability to anemia. Education about anemia and its prevention, as well as supplementation with iron tablets, is one solution to prevent and reduce the prevalence of anemia in females. Pesisir Selatan, a district in West Sumatra Province, recorded an increase in anemia prevalence in 2019. Based on this, it is necessary to provide education on anemia and its prevention to adolescent girls in the region. This counseling activity aimed to improve the knowledge and attitudes of adolescent girls regarding anemia. The activity consisted of pre-tests, counseling sessions, and post-tests. Counseling was conducted using lecture methods and interactive discussions with participants. Based on the evaluation of pre-test and post-test results, it was found that the counseling method was effective in increasing participants' knowledge. This was evidenced by a significant increase in participants' knowledge about anemia (p=0.004). The number of participants with good knowledge increased from 3 individuals (13.6%) to 7 individuals (31.8%), and none of the participants had poor knowledge after the counseling session. However, it was found that the counseling method did not significantly improve participants' attitudes towards anemia. In conclusion, although it did not affect participants' attitudes, the counseling method effectively enhanced their knowledge about anemia and is expected to help prevent anemia among adolescent girls